GEOCHEMISTRY AND TECTONIC SETTING OF METAMORPHIC SOLE ROCKS AND MAFIC DIKES FROM THE PINARBAŞI (KAYSERI) OPHIOLITE, CENTRAL ANATOLIA (TURKEY) - Vergili, Özden; Parlak, Osman (Ofioliti, 2005)
The Pinarbaşi ophiolite is located in Central Anatolia and emplaced onto the Tauride platform in Late Cretaceous. It comprises remnants of lower part of oceanic lithosphere, namely mantle tectonites tectonically underlain by high-grade metamorphic sole rocks and ultramafic to mafic cumulates. Number of isolated microgabbro-diabase and pyroxenite dikes cut the mantle tectonites at different structural levels. The mantle tectonites are dominated by harzburgite and dunite, whereas the cumulates consist of wehrlite, clinopyroxenite, olivine gabbro, troctolite and gabbronorite. The metamorphic sole rocks in the Pinarbaşi ophiolite crop out as thin slices beneath the sheared serpentinites and display inverted metamorphic gradient from amphibolite to greenschist facies. The rock types in the metamorphic sole are calcschists, epidote + plagioclase + amphibole schists, plagioclase + amphibole schists, amphibole schists, plagioclase amphibolites, amphibolites. The isolated microgabbro-diabase dikes are tholeiitic in character (Nb/Y = 0.03-0.07). The REE patterns, multi-element and tectonomagmatic discrimination diagrams suggest that the isolated dikes formed in a subduction-related environment. The metamorphic sole rocks exhibit two distinct geochemical features. The first group is alkaline (Nb/Y = 1.5-2.6), whereas the second group is tholeiitic (Nb/Y = 0.05-0.22) in nature. The REE patterns, multi-element and tectonomagmatic discrimination diagrams suggest that the protholith of the first group is similar to within-plate alkali basalts, whereas the second group is more akin to island arc tholeiitic basalts. All the evidences suggest that the Pinarbaşi ophiolite and the isolated dikes formed in a suprasubduction zone tectonic setting. The alkaline amphibolites were formed as a result of metamorphism of the seamount type basaltic rocks in intraoceanic subduction zone whereas the tholeiitic amphibolites were formed as result of intraoceanic thrusting in a supra-subduction zone (SSZ) basin during the closure of the Inner Tauride Ocean in Late Cretaceous.